The Role of Accounting Information Technology in Reducing Tax Evasion: an Applied Study on a Sample of Employees of Tax Departments in Middle AL -Furat AL –Awsat - Ali Sahib Noor (Harmoni Economics: International Journal of Economics and Accounting, 2024)
The current research aims to measure the role of accounting information technology represented by (Perceived benefit, ease of use) in reducing tax evasion represented by (Fair distribution of tax burden, penalties and penalties, combating tax evasion, employees efficiency, economic conditions) among a sample of employees of tax departments in the Middle Euphrates region, the research has stood on an important problem, which was formulated under the question of the research (What is the role of accounting information technology in reducing tax evasion?), In order to address the problem, two hypotheses were formulated, and the research relied on the descriptive analytical approach in measuring, describing and analyzing the research variables, and the research relied on the questionnaire tool in collecting the necessary data, As (150) questionnaires were distributed to the concerned tax department employees, and (137) questionnaires were retrieved, with (129) questionnaires valid for analysis and (8) damaged questionnaires. To analyze the results, the (SPSS&AMOS) package was used (V.28). The research summarized several findings, foremost of which was that accounting information technology has an impact in reducing tax evasion. Additionally, there is a high degree of use of accounting information technology in improving the capabilities of tax department employees in the Middle Euphrates region to reduce tax evasion. The research recommends the use of modern accounting information methods and techniques to combat tax evasion and ensure timely payment of taxes in the right place.